The Antagonism Mechanism Of Trichoderma spp. Towards Fusarium solani Mold - Utami Sri Hastuti; Indriana Rahmawati (Chemistry Department, The University of Brawijaya, 2016)
The antagonism ability of seven Trichoderma isolates towards F.solani have been observed and tested by dual culture technique. The antagonism mechanism observed by microscopic observation with light microscope and Scanning Electron Microscopy (SEM). The research result showed seven species of Trichoderma molds have different antagonism ability towards F.solani each other. The antagonism mechanism observed by light microscope and Scanning Electron Microscopy were mycoparasitism, antibiosis, and competition.Key word: antagonism mechanism, Trichoderma spp, F. solani, microscopic observation